TINJAUAN HUKUM PRINSIP SAFEGUARD DALAM PROTEKSI PRODUK PERTANIAN INDONESIA - Ega , Raden Galihati Hasan Saputra; Ahmad Jaka Santos Adiwijaya; Edy Santoso (Universitas Djuanda, 2024)
This journal discusses the principles of safeguards in protecting Indonesian agricultural products from surges in imports of agricultural products when it is expected to cause serious harm to the domestic industry in terms of International Trade Law and further elaboration in Indonesian National Law. This study uses a normative legal approach, namely using a literature study in the form of a review of the literature. The application of safeguards to Indonesian agricultural products can be done by setting the amount of import duty rates or setting import quota restrictions and setting time limits. The Indonesian government always seeks to harmonize domestic laws and regulations with international regulations for the protection of domestic farmers and industries in the context of food sovereignty, facilitating trade and increasing exports and preventing trade disputes in international forums.